ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN TERJADINYA RETURN OF SPONTANEOUS CIRCULATION PADA PASIEN HENTI JANTUNG DI IGD RSUD Dr ISKAK TULUNGAGUNG - Winanda Rizki Bagus Santosa* Titin Andri Wihastuti** Ali Haedar*** (The Indonesian Journal of Health Science, 2016)
The incidence of cardiac arrest in the world rise. Someone who is being treated in hospital emergency room has particular on the risk of cardiac arrest. The average number of patients presenting to the emergency room RSUD Dr Iskak Tulungagung a year is 32.140 patients, the average patient in the emergency room a day reached 89 patients. Patients emergency are said to be as many as 18.176 patients. Within a week from 13  patient happens ROSC after cardiac arrest as many as 6 patients (46%), 7 patients (54%) died. This study aimed to determine the factor associated with the occurrence of ROSC in patients with cardiac arrest. This study is a type of quantitative study. The design used in this study is correlational with cross sectional approach. Samples were collected by filling out a registry of PAROS. The sample by using accidental sampling with a sample obtained 45 patients. The results showed that the factor most associated with the ROSC on cardiac arrest is a heart rhythm (p 0.112), use of advanced airway before ROSC (p 0.062), and the use of mechanical CPR (p 0.000).Factor associated with the occurrence of ROSC in cardiac arrest is a heart rhythm, the use of advanced airway before ROSC, the use of mechanical CPR. The number of patients with cardiac arrest in the RSUD Dr Iskak Tulungagung happened ROSC smaller than the patients who did not happen ROSC